(untitled) (Ustozlar uchun, 2025)
In today’s globalized world, proficiency in the English language has become increasingly important for personal, academic, and professional success. This paper explores the significance of learning English, highlighting its role as a global lingua franca, its impact on career opportunities, and its importance in accessing information and technology. The study also addresses the challenges faced by non-native speakers and the benefits of English language education. By analyzing current trends and the necessity of English in various sectors, this paper aims to underscore the relevance of English language skills in enhancing communication and fostering international collaboration.